Adaptasi Morfologi Fisiologi dan Anatomi Eceng Gondok (Eichhornia crassipes (Mart) Solm) di Berbagai Perairan Tercemar - Haryanti, Sri; Hastuti, Rini Budi; Hastuti, Endah Dwi; Nurchayati, Yulita (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
The research was conducted to determine the morphology , physiology and anatomy adaptation from eceng gondok in waste water pollution. The research was done at the laboratory of Botany Structure and function. The design of the experiment use was split plot design based of Completely Randomized Design. First factor was density 2 and 4, second factor was 3 waste was LIK, drugs and metal foundry with water to control. The treatment was 3 replicates, The experiment was long 20 days with leaf morphology parameter ,growth/ physiology parameter ( long root, content of chlorophyl leaf) and anatomy parameter ( leaf,and stalk leaf and root). The result of the research indicated was leaf morphology adaptation on drugs waste and physiology adaptation on third waste and root anatomy adaptation was drugs waste with protrution branch root.